Numerical thermo-mechanical strength analysis of an IC engine component - Ali, Mohammed Ali Nasser; Hussein, R.A.; Hussein, H.A. (Zielona Góra: Uniwersytet Zielonogórski)
This research investigates a thermo-mechanical strength of three geometrical shape designs of an internal combustion (IC) engine piston by a finite element analysis (FEA). FEA was performed using Solidworks software for modelling geometrical piston designs, and the models were imported into ANSYS software for thermo-mechanical fatigue simulation.
Keywords: numerical analysis; IC engine piston; geometrical shape; thermo-mechanical strength; stress intensity and fatigue life